2017
DOI: 10.1155/2017/5714608
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Hedgehog Signaling Pathway in Regulating the Behavior of Germline Stem Cells

Abstract: Germline stem cells (GSCs) are adult stem cells that are responsible for the production of gametes and include spermatogonial stem cells (SSCs) and ovarian germline stem cells (OGSCs). GSCs are located in a specialized microenvironment in the gonads called the niche. Many recent studies have demonstrated that multiple signals in the niche jointly regulate the proliferation and differentiation of GSCs, which is of significance for reproductive function. Previous studies have demonstrated that the hedgehog (Hh) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…15 This also provides a novel strategy for preserving fertility. While several studies recently revealed the regulatory mechanisms underlying FGSC differentiation, 3,[16][17][18][19][20] proliferation, 4,[21][22][23][24] and apoptosis, 21,25 which are considered crucial for female fertility, other biological processes such as autophagy and its mechanism in FGSCs are largely unknown, and the use of small compounds may help us to understand them further.…”
Section: Introductionmentioning
confidence: 99%
“…15 This also provides a novel strategy for preserving fertility. While several studies recently revealed the regulatory mechanisms underlying FGSC differentiation, 3,[16][17][18][19][20] proliferation, 4,[21][22][23][24] and apoptosis, 21,25 which are considered crucial for female fertility, other biological processes such as autophagy and its mechanism in FGSCs are largely unknown, and the use of small compounds may help us to understand them further.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that there are multiple signaling pathways involved in the proliferation and differentiation of OGSCs, and the occurrence of the decline of ovarian function maybe associated with the loss of OGSCs. Supplementation of OGSCs may have a role in remodeling ovarian function [ 41 43 ]. These findings have important implications for the reproductive capacity of female mammals and the treatment of germ cell-related diseases, and provide new directions for the treatment of ovarian function decline after chemotherapy for scientists.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its widespread distribution and expression in three key signalling centres in vertebrate embryos (the notochord, the floor plate and the zone of polarizing activity), Shh is the most extensively studied vertebrate Hh family member. Yet, all Hhs activate the same conserved signalling pathway downstream of Ptc receptors to regulate embryonic patterning in vertebrate and invertebrate embryos [ 19 , 20 ], as well as stem and progenitor cell populations in the adult [ 21 , 22 ]. Shh misexpression leads to several forms of cancer [ 23 ], and loss of Shh function causes developmental midline defects in mice, chicks and humans [ 24 , 25 , 26 , 27 ].…”
Section: Conserved Post-translational Hh Lipidationmentioning
confidence: 99%